2009
DOI: 10.1103/physrevlett.102.196102
|View full text |Cite
|
Sign up to set email alerts
|

Phase Contribution of Image Potential on Empty Quantum Well States in Pb Islands on the Cu(111) Surface

Abstract: We use scanning tunneling spectroscopy to explore the quantum well states in the Pb islands grown on a Cu(111) surface. Our observation demonstrates that the empty quantum well states, whose energy levels lie beyond 1.2 eV above the Fermi level, are significantly affected by the image potential. As the quantum number increases, the energy separation between adjacent states is shrinking rather than widening, contrary to the prediction for a square potential well. By simply introducing a phase factor to reckon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 34 publications
(31 reference statements)
5
40
0
Order By: Relevance
“…Note that the field E = 0.05 eV/a 0 corresponds to a tip-surface distance as large as 4 nm for a bias of 4 eV. The actual electric fields obtained with the WPP for the conditions of constant current STS experiments (see below) of Yang et al 21 are also shown in Fig. 4.…”
Section: A Effect Of the Tip: Stark Shiftmentioning
confidence: 88%
See 4 more Smart Citations
“…Note that the field E = 0.05 eV/a 0 corresponds to a tip-surface distance as large as 4 nm for a bias of 4 eV. The actual electric fields obtained with the WPP for the conditions of constant current STS experiments (see below) of Yang et al 21 are also shown in Fig. 4.…”
Section: A Effect Of the Tip: Stark Shiftmentioning
confidence: 88%
“…Note that in Ref. 21 the labels n exp differ from the present definition of n as n exp = n − 1. However, n exp were not directly obtained but were deduced from the modeling of the data with the phase accumulation model.…”
Section: B Sts Spectramentioning
confidence: 89%
See 3 more Smart Citations